Endometrial carcinoma: clinicopathologic - Díaz, Juan (2015)
Thirty-eight patients with diagnosis of endometrial cáncer histologically demostrated were studied in order to identify the clinical features and determine the clinical stage. The patients were admitted at Belen Hospital, Trujillo, Perú, between 1966 and 1996. The mean age was 53,1 ± 11,4 years (range, 22 to 83 years); menarchie presented at 13,4 ± 1,6 years and menopause (n=25) at 48,2 ± 2,6 years. Eleven patients were nulliparae (28,9%), five (13,2%) had polycystic ovary, four (10,5%) had previous history of hypertension, two (5,3%) were diabetic and two (5,3%) bad personal history of another primary cáncer. Mean time of disease was 17,9 months. Most common, symptoms were vaginal bleeding (89,5%) and pelvic pain (52,6%) and most frequent sign was enlargement of the uterus (44,7%). The accuracy of the endometrial biopsy (n=5) and dilatation plus curettage was 80% and 85,7%, respectively. Papanicolaou was negative in 12 of 13 patients in stage I. According to the FIGO, 73,7% of the patients were in stage I, 15,8% in stage III, 7,9% in stage IV and 2,6% in stage II. Adenocarcinoma was the most frequent histologic type (75,7%), followed by adenoacanthoma (8,1%). Among the patients in stage I, 18 cases had well differenciated carcinomas and 10 cases were moderately or poorly differenciated carcinomas. Early diagnosis and properly staging are needed for optimum therapy of the endometrial cáncer.